Pengaruh Produk dan Harga terhadap Keputusan Pembelian Tepung Bumbu Mamasuka - Dodi Agusra (COSTING : Journal of Economic, Business and Accounting, 2018)
Companies must be responsive in addressing consumer behavior by anticipating changes and retaining consumers so that consumers are loyal. The aim of this research was to determine the effect of products and prices on consumer’s purchasing decisions Mamasuka spacy flour at PT Jico Agung in Pekanbaru. There were 60 consumers used as population and sample in this research. They are the consumers from shops and grocers selling Mamasuka spicy flour of PT Jico Agung in Pekanbaru. While the method used in this research was multiple linear analysis. The result showed that both products and prices affected each other in consumers’ decision to buy Mamasuka spicy flour. Product and prices also affected positively consumers’ purchasing decision in buying Mamasuka spicy flour at PT Jico Agung in Pekanbaru. The contribution of product and prices to consumers’ purchasing decisions in buying Mamasuka was 41,6%, while the rest is equal to 58,4% influenced by other variables not examined in this research. PT Jico Agung was expected to improve product quality and provide competitive price as well as concern about promotion strategi used.Keywords: Products, Prices, Purchasing Decisions